Acknowledging Montessori Education — a Research Perspective of Montessori's Legacy for the Future: Symposium Report - Ahlquist, Eva-Maria Tebano; Courtier, Philippine; Denervaud, Solange; Gynther, Per Wilhelm; Jendza, Jaroslaw; Quarfood, Christine (Journal of Montessori Research, 2024)
On 6 May 2022, 70 years after Maria Montessori’s death, Stockholm University and the Department of Education and Didactics organized an international Montessori symposium. The idea was to present a breadth of research on Maria Montessori. The symposium dealt with Maria Montessori in the interwar period, an analysis of the history of ideas. Another presentation suggested possible research models to study this large field. The symposium also presented interpretations of Montessori’s writings that point her out as a visionary and pioneer in education for a sustainable world. An additional research area addressed was the potential of neuroscience to examine the effects of teaching theory and learning in Montessori education. Finally, this report describes a study on whether Montessori-inspired education compared to traditional education stands up in areas of socio-economic disadvantage.